Tegotae-Based Control Produces Adaptive Inter- and Intra-limb Coordination in Bipedal Walking - Owaki, Dai; Horikiri, Shun-ya; Nishii, Jun; Ishiguro, Akio (Frontiers in Neurorobotics, 2021)
Despite the appealing concept of central pattern generator (CPG)-based control for bipedal walking robots, there is currently no systematic methodology for the design of a CPG-based controller. To remedy this oversight, we attempted to apply the Tegotae approach, which is a Japanese concept describing how well a perceived reaction, i.e., sensory information, matches an expectation, i.e., an intended motor command, in the design of localized controllers in the CPG-based bipedal walking model. To this end, we developed a Tegotae function that quantifies the Tegotae concept. This function allowed us to systematically incorporate decentralized controllers into our bipedal walking model design. We designed a two-dimensional bipedal walking model using Tegotae functions that was subsequently implemented in simulations to verify the validity of the proposed design scheme. We found that our model can walk on both flat and uneven terrains, and confirmed that the application of the Tegotae functions in all of the joint controllers results in excellent adaptability to environmental changes.